Earned Value Analysis on the Tayan Bulking Station Project in East Kalimantan - Yohanes Godman Ora Etlatius Woda Sidi; Masca Triana (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the cost and schedule performance and to estimate the final cost and completion time of the Tayan Bulking Station Project in West Kalimantan. The method used is Earned Value Analysis (EVA) by analyzing three main parameters: Budgeted Cost of Work Scheduled (BCWS), Budgeted Cost of Work Performed (BCWP), and Actual Cost of Work Performed (ACWP). Secondary data was obtained from PT. Sarana Remaja Mandiri, including the budget plan, S-curves, and weekly progress reports up to the 23rd week. The analysis continued by calculating variances (SV, CV), performance indices (SPI, CPI), and final estimates (EAC, ETC, ETS, EAS). The results indicate that the project's cost performance fluctuated. In the early project stages (weeks 1-9), there was a cost overrun (CPI < 1). However, in the subsequent period (weeks 10-23), cost performance improved significantly with cost efficiency (CPI > 1, reaching 2.35). Overall, the estimated final cost (EAC) is IDR 34.99 billion, which aligns with the initial budget (BAC). On the other hand, schedule performance tended to be delayed (SPI < 1) for most of the observation periods (weeks 1-14 & 18-23), although there was acceleration in weeks 15-17. The estimated project completion time (EAS) is 35 weeks, indicating a 1-week delay from the planned schedule of 34 weeks. The Earned Value method proved effective in identifying project performance. It is concluded that the Tayan Bulking Station Project is efficient in terms of cost but inefficient in terms of time, with a final delay of one week. This study recommends a greater focus on schedule control and improvement for this project and similar future projects.